Intangible Cultural Heritage (ICH): Understanding and manifestations - Abu Bakar, Aishah; Mohamed Osman, Mariana; Bachok, Syahriah (2011)
This paper reviews the theory, significance and expressions of Intangible Cultural Heritage. The term heritage has a broad meaning. It is understood that heritage is anything handed down from the past which ranges from natural to manmade elements. The entities of heritage are often categorized into two which are Tangible and Intangible heritages. The realization of the importance of intangible heritage began when disappearing traditions persisted due to failure in cultural reproduction. It is not until 1952 that UNESCO began the effort to establish methods of protecting what is now known as Intangible Cultural Heritage. In order to safeguard Intangible Cultural Heritage, the heritage must be relevant and practiced within the cultured community. In 2003, UNESCOIntangible Cultural Heritage Convention has proposed five broad domains of Intangible Cultural Heritage which are Oral traditions and expressions, Performing arts; Social practices, rituals and festive events; Knowledge and practices concerning nature and the universe; and Traditional craftsmanship. This paper discusses the history, significance and importance of Intangible Cultural Heritage in the built environment and how they are inculcated into universal understanding and manifestations.